Meta-synthesis regarding the progress of research in neuro-education within the field of learning disabilities - AARAB, SARA (Revue Internationale du Chercheur, 2020)
The main objective of this article is to review the progress of research in neuro-education over the period 2007 to 2020. Thus, we proceeded by the method of meta-analysis inspired by the work of Beaucher and Jutras (2007). This method of analysis consists of summarizing the results of recent research on the causes of learning disorders. Selecting and filtering of articles based on inclusion and exclusion criteria reduced the number of selected items to 43 articles. Then, the pulsed coding elements of the selected studies were organized as a scientific matrix. The results show that neuro-education studies contribute to deepening the knowledge of the underlying causes behind the occurrence of learning disabilities. Research on dyslexia has suggested that low phonological decoding is the cause that hinders the learning of reading. Research on dyscalculia reveals that it is due to the dysfunction of some areas of the parietal cortex as well as working memory deficit. Research on ADAH demonstrated a lower-than-normal level of some proteins in brain areas specialized in managing motivation and reward. Research on autism spectrum disorder has revealed that autism spectrum disorder is associated with childhood development delay of mirror neurons.